2019
DOI: 10.5194/hess-2019-294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The significance of soil properties to the estimation of soil moisture from C-band synthetic aperture radar

Abstract: Abstract. Soil Moisture is a key variable in hydrology, weather and climate modelling. Research has been directed to the estimation of soil moisture over wide areas through a combination of modelling, in-situ measurement and remote sensing to improve the accuracy of hydrological and meteorological forecasting. For monitoring and controlling irrigation and other agricultural purposes, there is also a need to capture local variability. Significant soil moisture differences are observed between and within fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 100 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Soil moisture is affected by the soil texture (determines water holding capacity), topography (affects runoff and infiltration), land cover (influences evapotranspiration), and climate (precipitation, wind, humidity, and solar illumination) [12]. The paper of Beale et al [13] looks at the role of soil properties in the estimation of soil moisture from C-band SAR. It was show that information on the soil texture, organic matter content, surface temperature, land use and crop modelling are important inputs to the success of retrieving soil moisture at the field scale.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture is affected by the soil texture (determines water holding capacity), topography (affects runoff and infiltration), land cover (influences evapotranspiration), and climate (precipitation, wind, humidity, and solar illumination) [12]. The paper of Beale et al [13] looks at the role of soil properties in the estimation of soil moisture from C-band SAR. It was show that information on the soil texture, organic matter content, surface temperature, land use and crop modelling are important inputs to the success of retrieving soil moisture at the field scale.…”
Section: Introductionmentioning
confidence: 99%
“…We do not use pedotransfer functions explicitly since our models can learn the required mapping. Soil information is essential because it is related to maximum water holding capacity (porosity), infiltration and to some extent, evaporation rates, which are critical controls on water retention and storage (Beale et al, 2019;Pan et al, 2012). Soil information obtained from soil grids has been used as a proxy for the disaggregation of soil moisture in prior work (Leenaars et al, 2018;Montzka et al, 2018).…”
Section: ) Low Resolution Sources (I) Soil Gridsmentioning
confidence: 99%
“…ascending acquisitions are acquired for this region at 16:59 UTC and descending acquisitions at 05:25 UTC. Some investigations about the effects of dew on the backscatter in Lband have been performed in (Riedel et al, 2002) and (Beale et al, 2019). For C-Band, (Gillepsie et al, 1990) observed an increase of the backscatter for wheat and mentioned that the different ways in which dew is distributed on the plants could help with crop type identification by radar.…”
Section: Higher Ascending Backscatter In Pastures and Forest Classesmentioning
confidence: 99%